Compositions comprising selenium and use of same for the treatment and prevention of disease or conditions associated with mitochondrial dysfunction - Power, Ronan; Egan, Casey; Lan, Zi-Jian; Kwiatkowski, Stefan; Xiao, Rijin; Yiannikouris, Alexander; Jackson, Lewis Collen (2018)
The present application relates to compositions comprising selenium (e.g., selenium enriched yeast and selenium containing compounds obtained or derived therefrom) and methods of using the same to treat and inhibit obesity, diabetes and related conditions. In particular, the present application provides compositions comprising selenium enriched yeast (e.g., selenium enriched yeast comprising 2% or less inorganic selenium), selenium containing compounds present therein and/or derived therefrom, and methods of using the same to enhance mitochondrial activity and function (e.g., in skeletal muscle and liver) in a subject (e.g., as a therapeutic and/or prophylactic treatment for diabetes, obesity and related conditions).